Peran Komunikasi Organisasi Pondok Pesantren Ngalah Dalam Membangun Disiplin Dan Akhlak Santri Asrama A - Arif Romadhoni; Siti Muyasaroh (Al-Qolamuna: Journal Komunikasi dan Penyiaran Islam, 2025)
This study, entitled "The Role of Organizational Communication at Ngalah Islamic Boarding School in Building Discipline and Morals in Dormitory A Students," focuses on how organizational communication patterns are implemented within the boarding school and their impact on the character development of the students. A qualitative descriptive approach was used to provide an in-depth description of communication phenomena within the boarding school. Data were collected through three main techniques: observation, in-depth interviews, and documentation. Informants included dormitory administrators, religious teachers (ustadz/ustadzah), and students living in Dormitory A. Data analysis employed the Miles and Huberman interactive model, which encompasses data reduction, data presentation, and conclusion drawing. The results indicate that organizational communication in Dormitory A takes place in two main forms: formal and informal. Formal communication is reflected in the dissemination of rules, the holding of meetings, and the enforcement of rules that bind all students. Meanwhile, informal communication occurs in daily interactions, such as advice, personal guidance, and the role models demonstrated by the ustadz and dormitory administrators. These two forms of communication have been shown to complement each other in creating a conducive atmosphere within the boarding school. Formal communication fosters discipline and adherence to rules in students, while informal communication plays a role in fostering noble morals in accordance with Islamic boarding school values. Thus, organizational communication is a crucial instrument in shaping the holistic character of students. This research is expected to provide theoretical contributions to the development of organizational communication studies, as well as provide practical input for Ngalah Islamic Boarding School and similar educational institutions in designing more effective communication strategies for character development. Abstrak Penelitian ini berjudul “Peran Komunikasi Organisasi Pondok Pesantren Ngalah dalam Membangun Disiplin dan Akhlak Santri Asrama A”. Fokus penelitian diarahkan pada bagaimana pola komunikasi organisasi dijalankan di lingkungan pesantren serta dampaknya terhadap pembinaan karakter santri. Pendekatan yang digunakan adalah kualitatif deskriptif dengan tujuan menggambarkan secara mendalam fenomena komunikasi di pesantren. Data penelitian dikumpulkan melalui tiga teknik utama, yaitu observasi, wawancara mendalam, dan dokumentasi. Informan penelitian meliputi pengurus asrama, ustadz/ustadzah, serta para santri yang tinggal di Asrama A. Analisis data menggunakan model interaktif Miles dan Huberman, yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa komunikasi organisasi di Asrama A berlangsung dalam dua bentuk utama, yakni formal dan informal. Komunikasi formal tercermin melalui penyampaian aturan, pelaksanaan rapat, serta penegakan tata tertib yang mengikat seluruh santri. Sementara itu, komunikasi informal hadir dalam interaksi sehari-hari, seperti nasihat, bimbingan personal, hingga keteladanan yang diperlihatkan oleh ustadz dan pengurus asrama. Kedua bentuk komunikasi tersebut terbukti saling melengkapi dalam menciptakan suasana pesantren yang kondusif. Komunikasi formal menumbuhkan kedisiplinan dan kepatuhan santri terhadap aturan, sedangkan komunikasi informal berperan dalam pembinaan akhlak mulia sesuai dengan nilai-nilai pesantren. Dengan demikian, komunikasi organisasi menjadi instrumen penting dalam membentuk karakter santri secara utuh. Penelitian ini diharapkan memberikan kontribusi teoretis bagi pengembangan studi komunikasi organisasi, sekaligus menjadi masukan praktis bagi Pondok Pesantren Ngalah dan lembaga pendidikan serupa dalam merancang strategi komunikasi yang lebih efektif untuk pembinaan karakter.